'And lastly, one for Saint Blaise': bishops, widows and patronage in a lost Office of Reginold of Eichstätt. Issue 1 (April 2021) - ALTSTATT, ALISON
ABSTRACT: This article concerns a fragmentary Office for Saint Blaise found in D-PREk Reihe V G1, a late fourteenth-century antiphoner from the Benedictine convent of Kloster Preetz. Despite the late date of the source, compositional similarities between this office and the Saint Nicholas office support the possibility that the former may be a lost Office attributed to Bishop Reginold of Eichstätt (r. 966–91) by the chronicler Anonymus Haserensis. I argue that Reginold may have written both the Office for Saint Blaise and the recension of the passio on which it is based for Pia of Bergen (Biletrud, Duchess of Bavaria), whom the chronicler names as Reginold's patron. This theory is supported by a consideration of the historical position and practices of Ottonian aristocratic widows, the development of saints' cults in tenth-century Eichstätt and the text of the passio itself. These findings give new insight into the office compositions of Reginold of Eichstätt, the Ottonian veneration of Byzantine saints and female patrons' involvement in the liturgical arts and establishment of cults in the late tenth century. These findings also provide hints to the origin of the liturgy of Kloster Preetz, whose mother house has never been identified.